Parents knowledge and oral hygiene level of kindergarten students - Muljadi, Vania Arista; Mandalas, Henry; Monica, Grace (Padjadjaran Journal of Dentistry, 2017)
Introduction: Parents knowledge related to oral health behaviour in children. Parents introduced the habit of tooth brushing to their children and how to maintain good oral hygiene. The purpose of this study was to describe parents knowledge about tooth brushing and oral hygiene level in the kindergarten students. Methods: The study design was cross sectional research and descriptive observational. This study was conducted towards 25 students of Gymboree and Kidsville at Bandung, Indonesia, which consisted of 14 boys (56%) and 11 girls (44%). The data collection was done by giving questionnaires to parents and examination of student’s oral hygiene level by using PHP index. Results: Generally parents already have the good knowledge that supports the children oral hygiene level, but there were still 52% of parents who does not use the recommended techniques to brush the outer surface of the teeth and 64% of parents who does not use the recommended techniques to brush the tooth surface that face to the cheek. The oral hygiene level of Gymboree and Kidsville students were very good 0% (0), 32% good (0.1- 1.7), 60% medium (1.8-3.4), and 8% bad (3.5-5.0). Awareness of parents about tooth brushing and oral hygiene level of children were generally adequate, but were not fulfilling the standards of oral health recommended by dentist. Conclusion: Parents knowledge about oral hygiene were generally good and the oral hygiene of kindergarten student were in medium range.